Technological measuring channel for bremsstrahlung monitoring - Butenko, A.A.; Karasyov, S.P.; Pomatsalyuk, R.I.; Tenishev, A.Eh.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N.; Tsvetkov, I.I. (Вопросы атомной науки и техники, 1999)
For metrological support of radiation technological processes based on braking radiation (bremsstrahlung) of the electron accelerator necessary is continuous monitoring of next radiation parameters: energy stream and energy of bremsstrahlung (B), density of energy stream and transfer of energy of bremsstrahlung, rate of absorbed doze and absorbed doze of bremsstrahlung, in range of energy of braking photons 5..50MeV. For realization of these requirements the technological measuring channel with primary sensor in the form of wide aperture thin-walled ionization chamber was developed by authors. The structure and metrological characteristics of the channel are described in this paper.